Hypoxia preconditioned human adipose derived mesenchymal stem cells enhance angiogenic potential via secretion of increased VEGF and bFGF. (19th April 2013) - Liu, Linqi; Gao, Jianhua; Yuan, Yi; Chang, Qiang; Liao, Yunjun; Lu, Feng
Abstract Mesenchymal stem cells (MSCs) are adult multipotent cells found in bone marrow, adipose tissue, and other adult tissues. MSCs improve regeneration of injured tissues in vivo, but the mechanisms remain unclear. Typically, MSCs are cultured under ambient or normoxic conditions (21% O2). However, the physiological niches of MSCs have much lower oxygen tension. When used as a therapeutic tool to repair tissue injuries, MSCs cultured in standard conditions must adapt from 21% O2 in culture to <1% O2 in ischemic tissue. We have examined the effects of hypoxia preconditioning (1% O2) in human adipose derived mesenchymal stem cells (AD‐MSCs) to discover the conditions that best enhance their tissue regenerative potential. We demonstrate that AD‐MSCs respond positively to hypoxia compared with normoxia preconditioning, show decreased apoptosis even in severe microenvironmental conditions (such as a low‐serum medium), and an increased expression of the angiogenic factors, vascular endothelial growth factor and basic fibroblast growth factor. Human umbilical vein endothelial cells have higher vitality and lower apoptosis when cultured in medium taken from hypoxia‐preconditioned AD‐MSCs, as well as significantly increased capillary‐like structures with this medium on Matrigel. The data suggest that hypoxia preconditioned AD‐MSCs can improve tissue regeneration.